Motivation-Based Segmentation of Hiking Tourists in Taiwan - Sai-Leung Ng; Ming-Chien Hsu (Tourism and Hospitality)
Hiking is one of the most popular and significant recreational activities in natural settings, yet hiking tourists are often not distinguished from the broader population of nature-based tourists. This study aimed to identify distinct segments of hiking tourists based on their motivations and to explore the relationship between segmentation, motivations, and their satisfaction with the hiking experience. Using a questionnaire survey of 262 hiking tourists in Taiwan and multivariate statistical techniques, four hiking motives—“relaxation”, “social interaction”, “competence and exploration”, and “mental refreshment”—were identified, and four segments of hiking tourists—“mental refreshment seekers”, “social hikers”, “challenge seekers”, and “general purpose hikers”—were classified, respectively. While all segments reported high levels of satisfaction, their satisfaction was influenced by different motives. This study enhances the theoretical understanding of hiking motives and provides practical recommendations for enhancing hiking experiences and nature conservation.